Estimating Herbage Mass on Pastures to Adjust Stocking Rate - Jose Dubeux; Marcelo Wallau; Joao Vendramini; Liliane Silva; Jane Griffin; Nicolas DiLorenzo; Erick Santos (EDIS)
This new 6-page document explains methods to measure forage mass and utilize that information to estimate an adequate stocking rate. Written by Jose Dubeux, Marcelo Wallau, João Vendramini, Liliane Silva, Jane Griffin, Nicolas DiLorenzo, and Erick Santos, and published by the UF/IFAS Agronomy Department, June 2019. https://edis.ifas.ufl.edu/ag434